Aligned Epitaxial SnO2 Nanowires on Sapphire: Growth and Device Applications - Wang, Xiaoli; Aroonyadet, Noppadol; Zhang, Yuzheng; Mecklenburg, Matthew; Fang, Xin; Chen, Haitian; Goo, Edward; Zhou, Chongwu (Nano letters, 2014)
Semiconducting SnO2 nanowires have been used to demonstrate high-quality field-effect transistors, optically transparent devices, photodetectors, and gas sensors. However, controllable assembly of rutile SnO2 nanowires is necessary for scalable and practical device applications. Here, we demonstrate aligned, planar SnO2 nanowires grown on A-plane, M-plane, and R-plane sapphire substrates. These parallel nanowires can reach 100 μm in length with sufficient density to be patterned photolithographically for field-effect transistors and sensor devices. As proof-of-concept, we show that transistors made this way can achieve on/off current ratios on the order of 106, mobilities around 71.68 cm2/V·s, and sufficiently high currents to drive external organic light-emitting diode displays. Furthermore, the aligned SnO2 nanowire devices are shown to be photosensitive to UV light with the capability to distinguish between 254 and 365 nm wavelengths. Their alignment is advantageous for polarized UV light detection; we have measured a polarization ratio of photoconductance (σ) of 0.3. Lastly, we show that the nanowires can detect NO2 at a concentration of 0.2 ppb, making them a scalable, ultrasensitive gas sensing technology. Aligned SnO2 nanowires offer a straightforward method to fabricate scalable SnO2 nanodevices for a variety of future electronic applications.